International Financial Reporting Standards Adoption Strategies Effects on Supply Chain Management, Corruption and Accounting Quality: International Evidence - Abdullah Hammad Alhammad; Asna Abdullah Atqa; Ahmed Razman Abdul Latiff; W.N.W. Azman-Saini (International Journal of Supply Chain Management, 2020)
Abstract- The empirical literature on the effects of International Financial Reporting Standards (IFRS) adoption strategies on supply chain management and accounting quality focuses on more IFRS enforcement strategy. Limited studies have, in particular, examined IFRS modification strategy in relationship with accounting quality. In this regard, this paper investigates the impacts of different IFRS adoption strategies on accounting quality. The mediating effect of control of corruption on the relation between different IFRS adoption strategies on accounting quality is also examined. The paper uses the two step system GMM estimator with a sample of 35 countries for the periods that span from 2013 to 2017. The findings reveal that different IFRS adoption strategies have significant influences on accounting quality. The different IFRS adoption strategies, namely enforcement and modification are positively associated with accounting quality with measure of timely loss recognition (?1 = 0.190, p 0.001) and (?2 = 0.189, p 0.001), respectively. These findings are consistent with the prior studies. The findings underline the importance of distinction between different IFRS adoption strategies. Furthermore, control of corruption is found to mediate the associations between different IFRS adoption strategies and quality of accounting, indicating accounting quality is related to control of corruption, which in turn is affected by both IFRS enforcement and modification strategies. Additionally, the accounting quality is strongly improved by IFRS enforcement and modification through the control of corruption as mediation. This implies that the control of corruption in a given nation by consdring the SCM, improves in accounting quality more than IFRS adoption strategies. These findings provide flesh insights to stakeholders and contribute to accounting quality literature.